Airborne observations reveal the fate of the methane from the Nord Stream pipelines - Friedemann Reum; Julia Marshall; Henry C. Bittig; Lutz Bretschneider; Göran Broström; Anusha L. Dissanayake; Theo Glauch; Klaus-Dirk Gottschaldt; Jonas Gros; Heidi Huntrieser; Astrid Lampert; Michael Lichtenstern; et al. (Nature Communications)
Abstract The Nord Stream pipeline leaks on 26 September 2022 released 465 ± 20 kt of methane into the atmosphere, which is the largest recorded transient anthropogenic methane emission event. While most of the gas escaped directly to the atmosphere, a fraction dissolved in the water. So far, studies on the fate of this dissolved methane rely on pipeline volumetric estimates or spatially sparse concentration measurements and ocean models. Here, we use atmospheric measurements with broad spatial coverage obtained from an airborne platform to estimate outgassing of 19-48 t h−1 on 5 October 2022. Our results broadly agree with ocean models but reveal uncertainties such as inaccuracies in their spatial emission distribution. Thus, we provide a data-driven constraint on the fate of the methane from the Nord Stream pipelines in the Baltic Sea. These results demonstrate the benefit of a fast-response airborne mission to track a dynamic methane emission event.